OUR LINK WITH NOBELâ€™S WILL - Badar, Ahmed (Pakistan Journal of Physiology, 2010)
On 27th November 1895, Alfred Nobel signed his last will and testament, giving the largest share of his fortune to a series of prizes, the Nobel Prizes. As described in Nobelâ€™s will, one part was dedicated to â€œâ€¦the person who shall have made the most important discovery within the domain of physiology or medicineâ€.1 There have been numerous â€˜non conclusiveâ€™ discussions about many points related to this will, like: Why Nobel specifically picked up Physiology? Why Physiology and Medicine were bracketed together? Why no other field in medicine was nominated? What was the domain of Physiology in Nobelâ€™s era? â€¦ and so on. The fact is this that a Physiologist takes pride in mentioning that there is a specified prize for Physiology. It makes us think that we Physiologists are linked to a great subject that has an enormous contribution in human history. Where is the problem then? It is high time to bring our head out of sand and look around us to find what is wrong with us. Do we have an inferior brain make up? Is there a â€˜Physiology & Medicine Research geneâ€™ missing in us? Are we not properly trained? Are we not motivated? Are we not interested in research that is for contribution to knowledge only? Do we just want to complete our papers required for promotions or tenure tracking by replicating or so called â€˜verifyingâ€™ othersâ€™ work? Do we have our own laboratory or corner in a laboratory? Are we afraid of computer based laboratories? How often do we read latest articles? How many postgraduate students have we trained? Have we properly motivated our undergraduate and postgraduate students for research? Are we encouraging our juniors to take lead? Are topics in research finished? Have we found cure for hypertension and diabetes? Are we depressed that we cannot bring up new ideas for research? Are we really empty-handed after departure of biochemistry, pharmacology, genetics, immunology, haematology and neurology from our folds? Or have we surrendered completely that research in Physiology & Medicine is to be done by the scientists in a handful of countries only and we have to just â€˜applyâ€™, â€˜replicate in our settingsâ€™ or â€˜verifyâ€™ their work? Are we the proud Physiologists that Nobel mentioned in his will? Are we really linked to the Nobelâ€™s will?